West African agriculture and climate change: A comprehensive analysis - Benin - Lawin, Emmanuel A.; Akponikpè, P. B. Irénikatché; Jalloh, Abdulai; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
This summary note is an excerpt from the chapter on Benin that will appear in the peer-reviewed IFPRI monograph, West African Agriculture and Climate Change: A Comprehensive Analysis.